Influência das embalagens no controle do gorgulho Callosobruchus analis em feijão de corda, Vigna sinensis - Magalhaes, J.A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Different containers were used for the control of Callosobruchus analis Fabr., in cowpeas (Vigna sinensis Endl). The following deposits were used: cup closed with cloth; cloth bag; closed cans sealed or not with bee wax; bottle closed with cork and polyethylene bag with different thicknesses. The gaseous interchange between container and outside was an important factor in the growth of C. analis Fabr.